Physiological Responses to Acute Cycling With Blood Flow Restriction - Kilgas, Matthew A.; Yoon, Tejin; McDaniel, John; Phillips, Kevin C.; Elmer, Steven J. (Frontiers in Physiology, 2022)
Aerobic exercise with blood flow restriction (BFR) can improve muscular function and aerobic capacity. However, the extent to which cuff pressure influences acute physiological responses to aerobic exercise with BFR is not well documented. We compared blood flow, tissue oxygenation, and neuromuscular responses to acute cycling with and without BFR. Ten participants completed four intermittent cycling (6 × 2 min) conditions: low-load cycling (LL), low-load cycling with BFR at 60% of limb occlusion pressure (BFR60), low-load cycling with BFR at 80% of limb occlusion pressure (BFR80), and high-load cycling (HL). Tissue oxygenation, cardiorespiratory, metabolic, and perceptual responses were assessed during cycling and blood flow was measured during recovery periods. Pre- to post-exercise changes in knee extensor function were also assessed. BFR60 and BFR80 reduced blood flow ( 33 and 50%, respectively) and tissue saturation index ( 5 and 15%, respectively) when compared to LL (all p < 0.05). BFR60 resulted in lower VO2, heart rate, ventilation, and perceived exertion compared to HL (all p < 0.05), whereas BFR80 resulted in similar heart rates and exertion to HL (both p > 0.05). BFR60 and BFR80 elicited greater pain compared to LL and HL (all p < 0.05). After exercise, knee extensor torque decreased by 18 and 40% for BFR60 and BFR80, respectively (both p < 0.05), and was compromised mostly through peripheral mechanisms. Cycling with BFR increased metabolic stress, decreased blood flow, and impaired neuromuscular function. However, only BFR60 did so without causing very severe pain (>8 on pain intensity scale). Cycling with BFR at moderate pressure may serve as a potential alternative to traditional high-intensity aerobic exercise.